2008
DOI: 10.1063/1.2938090
|View full text |Cite
|
Sign up to set email alerts
|

Structural ordering in CdxPb1−xF2 alloys: A combined molecular dynamics and solid state NMR study

Abstract: Molecular dynamics (MD) simulations of binary Cd(x)Pb(1-x)F(2) alloys have been carried out, using a two-body Buckingham interaction potential, leading to a correct description of structural properties as a function of composition and pointing towards an understanding of the eutectic phenomenon. The simulation data can be analyzed in terms of five local fluorine environments Q((n)) (4> or =n> or =0), where n is the number of Pb nearest-neighbor environments. The results suggest a highly nonstatistical populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 19 publications
6
16
0
Order By: Relevance
“…19 F MAS NMR provides an ideal method to probe the local order in fluoride solid solutions. 50,[57][58][59][60][61][62][63][64] Nevertheless, the case of the La 1−x Ba x F 3−x solid solution seems to be, at first sight, unfavorable since there are three fluorine sites in LaF 3 and since the δ iso value of BaF 2 (−14.3 ppm, 56 CN = 4, 2.683 Å 65 ) is in the range of the δ iso values of LaF 3 . Moreover, local disorder, leading to a broadening of the NMR lines, is expected since the heterovalent substitution generates fluorine vacancies and that both cations have different ionic radii.…”
Section: F Solid State Nmr Analysismentioning
confidence: 99%
“…19 F MAS NMR provides an ideal method to probe the local order in fluoride solid solutions. 50,[57][58][59][60][61][62][63][64] Nevertheless, the case of the La 1−x Ba x F 3−x solid solution seems to be, at first sight, unfavorable since there are three fluorine sites in LaF 3 and since the δ iso value of BaF 2 (−14.3 ppm, 56 CN = 4, 2.683 Å 65 ) is in the range of the δ iso values of LaF 3 . Moreover, local disorder, leading to a broadening of the NMR lines, is expected since the heterovalent substitution generates fluorine vacancies and that both cations have different ionic radii.…”
Section: F Solid State Nmr Analysismentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2014 tentatively attributed to uoride ions next to one La 3+ species, while the resonance near À31 ppm might be assignable to interstitial uoride ions, resembling the F 1 and/or F 2 sites reported in ref. 26 and having proximity to two lanthanum species. Based on these assignments, we observe that the signal displacements relative to F n are generally larger here than those in Y-doped CaF 2 .…”
Section: Vuv Spectroscopymentioning
confidence: 99%
“…25 In contrast, clear segregation and clustering phenomena were observed in the PbF 2 -CdF 2 system. 26 Furthermore, a detailed 19 F MAS NMR study by Wang and Grey showed that aliovalent substitution in the CaF 2 -YF 3 system creates multiple uoride environments. 27 The quantitative concentrations of these environments have been discussed in relation to various defect cluster models originating from the necessary creation of interstitial uoride ions owing to charge balancing constraints.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to obtain some information regarding the nature of the eutectic phenomenon by examining other research areas. The eutectic phenomenon has been studied in alloys, glasses, biological compounds, and deep eutectic systems. , A common observation in these studies is that the lower melting point is indicative of greater molecular mobility . As well, the eutectic behavior of these systems has been attributed to differences in intermolecular interactions, particularly hydrogen bonds …”
Section: Introductionmentioning
confidence: 99%